Application Specific Instruction Set Processor (ASIP) Design In An 8-Bit Softcore Microcontroller - Salim, Sani Irwan; Soo, Yew Guan; Samsudin, Sharatul Izah (Penerbit Universiti, UTeM, 2018)
The microcontroller-based system is currently having a tremendous boost in demand in line with the Industrial Revolution 4.0. Although more applications seem to concentrate on software algorithms and wireless connectivity, the hardware side of the system is still occupied by microcontroller variants. With huge alternatives being offered to setup a microcontroller system, having a softcore microcontroller is extremely beneficial especially when considering the rapid advancement in computer technology. Although the 8-bit microcontroller has less computational capability compare to other high-end microcontroller families, it has an advantage in low code density for I/O application and control. The purpose of this research is to combine the best feature of the 8-bit architecture together with efficient arithmetic operations in the implementation of moving average filter. The modules’ integration is implemented using ASIP design without occurring extra board space and is developed using the Field Programmable Gate Array (FPGA) as the single chip solutions. It was found that the revised microcontroller architecture has produced a faster execution time and similar maximum frequency when benchmarked with its predecessor. The overall ASIP design procedures used in this research provides flexibility for further development, either by extending its module to incorporate more complex algorithms or by upgrading current designs of its components.